ANALYSING THE OUTCOME OF BIRTH IN WOMEN WITH MULTIPLE PREGNANCY COMPLICATED BY TWIN-TO-TWIN TRANSFUSION SYNDROME - Gafurova N.O.; Ilyasov A.B.; Yusupbaev R.B. (Journals Park Publishing, 2022)
A multiple pregnancy which is two or more fetuses develop in the uterus. A multiple pregnancy is associated with a significant number of complications, one of which is the feto- fetal transfusion syndrome. Relevance: feto- fetal transfusion syndrome is accompanied by high perinatal mortality and morbidity, the number of cases of which ranges from 56 to 100%. Objective: to evaluate the perinatal outcomes of multiple pregnancies complicated by feto- fetal transfusion syndrome. Materials and methods: the analysis of the course of pregnancy and the outcome of childbirth in women with multiple pregnancies complicated by feto - fetal transfusion syndrome and uncomplicated twins was carried out. Results: during the study period, 1350 births occurred on the basis of the maternity hospital, of which 55 births were twins (4%). Among them, in 3 multiparous multiparous with multiple monochorionic biamniotic pregnancy, a complication was observed as feto-fetal transfusion syndrome, which is 5% of twins. All 3 pregnancies were complicated by antenatal death of the first fetus and premature birth. Conclusions: according to the study, multiple pregnancy complicated by feto-fetal transfusion syndrome is associated with a high risk of antenatal fetal death.
Keywords: multiple pregnancy, chorionicity, feto-fetal transfusion syndrome, donor, recipient, preterm birth.